Text structures and fables teaching students to write about what they read, grades 3-12 - Bernabei, Gretchen S.; Hover, Jayne (Thousand Oaks, California Corwin Literacy, 2023)
"The state test is changing in Texas. For the last 20 years, Texas students in grades 4, 7, 9 and 10 have been asked to write an essay in response to a stand-alone prompt like "What's your favorite season?" or "What's the importance of friendship?" But in the spring of 2023, this will all change. Now, the Texas legislature will be assessing reading and writing together. Students will no longer have stand-alone essays on the high-stakes tests, but will be asked to answer questions, both in short format and as more extended length. But the kicker is that now students will be tested on this writing at every grade from grade 3 to 10. This means that teachers of grades formerly tested only for reading will now have writing components at every grade level, sending Texas teachers and administrators into panic mode, as teachers of grades 3, 5, 6, and 8 have never received training for writing instruction. Text Structures and Fables: Writing About What We Read, is designed to meet this pressing need. Part I, Building Strong Readers and Writers and Part II, Assessing Strong Readers and Writers will assist not only ELA teachers, but also those teachers formerly known as "reading teachers." Additionally, the Texas Education Agency intends to eventually add short-answer questions on all tests, including social studies and science. Part III, Using Non-traditional formats to "Show me you read it," is to help those teachers add a non-threatening writing component into their coursework"--Provided by publisher.
Includes bibliographical references.
Keywords: Composition (Language arts) -- Study and teaching (Secondary) -- Activity programs; English language -- Composition and exercises -- Study and teaching (Elementary); Fables -- Study and teaching (Elementary); Fables -- Study and teaching (Secondary); Educational tests and measurements -- Texas